PENGELOLAAN BENDUNGAN SINDANGHEULA DALAM PERSEFEKTIF TAFSIR ILMI: INTEGRASI NILAI-NILAI AL-QUR’AN DENGAN KONSEP KEBERLANJUTAN SUMBER DAYA AIR - Yusroh, Yusroh; Rohmah, Siti; Hasbullah, M. Farrij; Abdurrahman, Haris; Fattah, M. Yusuf; Rosa, Andi (STAI Asy-Syukriyyah, 2025)
Water resource management in Indonesia has tended to be dominated by technocratic and sectoral approaches, without adequate integration with religious values that can contribute to ecological awareness. On the other hand, the approach of scientific interpretation in the Islamic tradition holds many rich and relevant sustainability principles. However, these principles have not been systematically utilized in environmental management policies, especially related to strategic infrastructure such as the Sindangheula Dam. This study aims to bridge the gap between epistemic and praxis in water resource management with the formulation of an integrative framework that links the values of the Qur'an through scientific interpretation and the concept of sustainability. Using a qualitative-contextual approach and thematic analysis methods to Qur'anic verses related to water, this study found that principles such as monotheism, trust, balance (al-mīzān), justice ('adl), and prohibition of waste (isrāf) have direct relevance to fair, participatory, and sustainable water governance practices. As a case study, the Sindangheula Dam is used to demonstrate the potential application of Qur'anic values in socio-technical and public policy contexts. The results of this study conclude that the interpretation of science is not only a hermeneutic approach, but also an axiological paradigm that can strengthen natural resource policies based on spiritual values and ecological sustainability. These findings open up opportunities to develop integrative studies between Islamic sciences, environmental science, and public policy in the context of sustainability.